Keanekaragaman dan Pola Sebaran Spesies Tumbuhan Asing Invasif di Cagar Alam Pulau Sempu, Jawa Timur - Abywijaya, Ilham Kurnia; Hikmat, Agus; Widyatmoko, Didik (JURNAL BIOLOGI INDONESIA, 2014)
The presence of invasive alien plant species has been known to cause various negative impacts on ecosystems in theinvaded conservation area. This research aims to identify diversity and distribution pattern of invasive alien plantsspecies in Sempu Island Nature Reserve, and to determine the most influential environmental factors to theirdispersion. The methods used were the combination of quantitative vegetation analysis and rapid assessmenttechnique followed by the principal component analysis. As many as 10 invasive alien plants species (belonging to 7families) have been identified within this conservation area, e.g., Pistia stratoites, Ageratum mexicanum, Vernoniacinerea, Cyperus rotundus, Passiflora foetida, Centotheca lappacea, Eleusine indica, Imperata cylindrica, Hedyotiscorymbosa, and Lantana camara. All invasive alien plant species found in the sampling plots had a clumpeddistribution pattern. The most influential environmental factors to the invasive alien plants dispersion were landslope and distance from shoreline.Keywords: distribution pattern, environmental factors, invasive alien plants, Sempu Island Nature Reserve